2020
DOI: 10.1002/jmv.26649
|View full text |Cite
|
Sign up to set email alerts
|

Comparing cytomegalovirus diagnostics by cell culture and quantitative nucleic acid testing in broncho‐alveolar lavage fluids

Abstract: Many clinical laboratories have replaced virus isolation in cell‐culture (VIC) for cytomegalovirus (CMV) by quantitative‐nucleic‐acid testing (QNAT), rendering clinically relevant CMV‐replication difficult to distinguish from CMV‐shedding or latent infection. We compared direct VIC in 1109 consecutive bronchoalveolar lavage fluids (BALFs) and a well‐validated CMV‐QNAT (Basel‐CMV‐UL111a‐77bp). In the retrospective Group 1 (N = 694) and Group 2 (N = 303), CMV‐QNAT was performed within 48 h from 2‐fold and 10‐fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
(107 reference statements)
0
15
0
Order By: Relevance
“…Three studies published in recent years also compare the results of viral culture and qPCR for HCMV detection in BAL uid. Based on an analysis of 1,109 BAL samples from immunosuppressed patients, Leuzinger et al (2020) determined that >10,000 copies/mL was an indicator of active replication. A limitation compared with the present study is that only shell vial culture was used, and not traditional culture; also, some of the samples (88%) were frozen and processed for qPCR analysis retrospectively, and the qPCR assay used was not fully automated (it required prior DNA extraction), which can reduce the reproducibility of the results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies published in recent years also compare the results of viral culture and qPCR for HCMV detection in BAL uid. Based on an analysis of 1,109 BAL samples from immunosuppressed patients, Leuzinger et al (2020) determined that >10,000 copies/mL was an indicator of active replication. A limitation compared with the present study is that only shell vial culture was used, and not traditional culture; also, some of the samples (88%) were frozen and processed for qPCR analysis retrospectively, and the qPCR assay used was not fully automated (it required prior DNA extraction), which can reduce the reproducibility of the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the absence of HCMV DNA in plasma does not exclude pneumonitis. Recently, two studies found that approximately one third of patients with HCMV pneumonitis had an undetectable plasma VL, demonstrating that local replication of the virus can occur in the lower respiratory tract without systemic involvement [11,14,19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations